Penerapan Metode Forward Chaining dalam Perancangan Sistem Pakar Tes Emotional Quotient (EQ) Berbasis Web - Anggia Dasa Putri; Ellbert Hutabri (Politeknik Negeri Batam, 2019)
Humans as social beings who must interact with various other individual character types must have emotional intelligence. Emotional intelligence is not the same person, intelligence is influenced by the family environment, age, and physical. High or low emotional intelligence influences how to interact and work. Individuals who have low emotional intelligence tend to have individualistic traits and cannot work together in teams, for that every company or agency needs to conduct tests on prospective employees. IQ and EQ tests conducted by companies to prospective employees so far have been done manually, so that problems often occur such as the test taker takes a long time to correct answer sheets, errors in calculating scores and reports of long test results when the test participants are in the amount big. Given the company's mistakes are often too late and wrong in making decisions to accept the right employees, for that we need to make an expert system that can help companies in conducting EQ tests for the selection process of prospective employees in accordance with the desired criteria. Expert system that is designed using the method of forward chaining is a method of searching or tracking information starting from existing information and combined with the rules to get a conclusion. Expert System Design uses an object oriented approach and PHP programming language so that it can be used to help companies, especially in the Human Resource Department (HRD) in the selection of prospective employees.